Prevalence of Posttraumatic Stress Symptoms and Associated Characteristics Among Patients With Chronic Pain Conditions in a Norwegian University Hospital Outpatient Pain Clinic - Linnemørken, Lene Therese Bergerud; Granan, Lars-Petter; Reme, Silje Endresen (Frontiers in Psychology, 2020)
Introduction: Comorbid posttraumatic stress disorder (PTSD) in patients with chronic pain may have a negative effect on the course and outcome of both disorders. Nevertheless, the co-occurrence of the two conditions is often overlooked in clinical settings. Further, little is known about how PTSD is associated with biopsychosocial characteristics in this patient group. The first objective was to assess the prevalence of posttraumatic stress symptoms (PTSS) in patients with chronic pain in a Norwegian university hospital outpatient pain clinic. The second objective was to investigate possible associations between PTSS and adverse outcomes such as pain intensity, disability and distress. The third objective was to compare the PTSS prevalence rates between primary versus secondary pain conditions. Materials and methods: 692 patients meeting for pain assessment completed self-report questionnaires about PTSS and possibly associated factors. The Life Events Checklist and the Stressful Life Events Screening Questionnaire were used to screen for potentially traumatic life events. The Impact of Events Scale – Revised and the PTSD Checklist for DSM-5 were used to assess PTSS. Differences between patients with and without severe PTSS on the possibly associated variables were analyzed by chi-squared- and t-tests. Results: 20,7% of the participants reported a level of PTSS qualifying for a PTSD diagnosis. These patients reported higher levels of pain intensity, pain bothersomeness, disability and psychological distress, as well as lower levels of self-efficacy. They also reported higher levels of pain catastrophizing, perceived injustice, fatigue, and sleep difficulties. Finally, there was not a significant difference in prevalence rates between primary and secondary pain conditions. Discussion: PTSS are frequent in patients with chronic pain, and a range of psychological characteristics is associated with a high level of such symptoms in this patient group. Patients with both conditions report a significantly higher symptom load, and the potential impact on the individual’s life is major. In terms of pain condition, there were no differences in PTSS between primary pain conditions and secondary pain conditions in this pain population. This study emphasizes the importance of increased attention on PTSS when seeing patients with chronic pain conditions in clinical practice.